An efficient solution for resolving iTRAQ and TMT channel cross‐talk. (29th April 2019) - Searle, Brian C.; Yergey, Alfred L.
Abstract: Isobaric tagging reagents such as isobaric tag for relative and absolute quantitation (iTRAQ) and tandem mass tag (TMT) typically have isotopic impurities that cause significant cross‐talk between channels. Here, we present an efficient solution to compensate for channel cross‐talk using linear algebra and find that it is between 20× and 120× faster than previous methods. We also find that the effects of channel cross‐talk are as important to manage as the effects of ratio compression because of precursor impurities, and we have released an open‐source tool to perform both types of calculations.